(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To analyze the current practice of Clopidogrel use in the treatment of acute coronary syndrome at Military Hospital 175. Subjects and methods: A prospective cross-sectional descriptive study was conducted on 110 hospitalized patients diagnosed with acute coronary syndrome who received Clopidogrel therapy at the Department of Cardiology, Military Hospital 175, from January 2024 to November 2025. Results: The study included 110 patients with acute coronary syndrome, predominantly male (77.3%), with a mean age of 65.2 ± 11.3 years. Dual antiplatelet therapy was predominantly used (96.4%), of which the combination of Aspirin and Clopidogrel accounted for the highest proportion (88.2%). The most commonly used loading-dose regimen was Aspirin 300 mg combined with Clopidogrel 300 mg (83.0%). The mean platelet aggregation after 6 days of maintenance-dose Clopidogrel was 42.0 ± 14.4%, with no significant difference between patients with ST-elevation myocardial infarction (42.6 ± 14.8%) and those with non-ST-elevation acute coronary syndrome (41.1 ± 13.9%) (p > 0.05). The overall rate of Clopidogrel resistance was 29.1%, which was comparable between the two clinical subgroups (p > 0.05). Conclusion: Clopidogrel is widely used in the management of acute coronary syndrome at Military Hospital 175, primarily as part of dual antiplatelet therapy. The degree of platelet inhibition and the rate of Clopidogrel resistance did not differ significantly among clinical presentations of acute coronary syndrome.